2012
DOI: 10.14527/c2s2m3
|View full text |Cite
|
Sign up to set email alerts
|

Teacher comments on the contributions of primary education curriculums to the reflective thinking abilities of students

Abstract: ÖzetYapılandırmacı öğrenme yaklaşımı temele alınarak hazırlanan 2005 ilköğretim programlarında öğrencilerin üst düzey düşünmelerinin geliştirilmesi büyük önem arzetmektedir. Üst düzey düşünme türlerinden birisi de yansıtıcı düşünmedir. Bu araştırma, ilköğretim birinci kademe programlarının öğrencilerin yansıtıcı düşünmelerini geliştirmeye katkısının öğretmen görüşleri doğrultusunda incelenmesi amacıyla yapılmıştır. Betimsel özellikte olan çalışmada tarama (survey) yönteminden yararlanılmıştır. Araştırma, Elazı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similar to this finding, Phan (2007) found that different methods and techniques used in the classroom environment affected the students' knowledge. In addition, Demiralp and Kuzu (2012) suggested that teachers were positively affected when students used interactive educational environments to reflect their knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, Phan (2007) found that different methods and techniques used in the classroom environment affected the students' knowledge. In addition, Demiralp and Kuzu (2012) suggested that teachers were positively affected when students used interactive educational environments to reflect their knowledge.…”
Section: Discussionmentioning
confidence: 99%